Influence of different carob fruit flours (Ceratonia siliqua L.) on wheat dough performance and bread quality - Salinas, Maria Victoria (2015)
The objective of this work was to study the influence of carob flours from seed germ (G) and from fruit pulp (P) fractions (from 10 to 30 % w/w) on hydration (moisture, water activity, and relaxation time) and rheological properties (farinograph, rheometry, texture) of wheat dough. Bread quality (specific volume (Vs), protein content, crumb texture, and moisture) was also analyzed. Farinogram shape of G and P samples were different. Water absorption of control flour (C) was lower than that obtained for carob germ-wheat flour blends, presenting wheat flour the highest development time. Dough hardness and adhesiveness increased with carob flour, mainly with G. Cohesiveness and springiness of C were higher than those observed for wheat-carob dough. Differences in dough microstructure for the different formulations were predicted by a G’ versus G^ plot; heterogeneity in polymer morphology was detected with high contents of carob flours. Even though breads with increasing levels of carob flour presented lower Vs and higher crumb firmness and chewiness than wheat bread, protein content for G breads was higher, converting this flour in an interesting ingredient for increasing protein nutrition. Protein value was slightly low for breads with pulp carob flour; nevertheless, fiber contribution would be high.